2020
DOI: 10.3389/fnins.2020.00887
|View full text |Cite
|
Sign up to set email alerts
|

Does Osteopathic Manipulative Treatment Induce Autonomic Changes in Healthy Participants? A Thermal Imaging Study

Abstract: Osteopathic manipulative treatment (OMT) has been demonstrated to be an effective therapy in several clinical conditions and age groups. Despite the clinical effectiveness, lack of robust data in terms of neurobiological, specifically autonomic, mechanisms of action is observed. Preliminary studies showed a parasympathetic effect leading to a trophotropic effect of OMT. However, these data are limited to heart rate variability (HRV) analysis. In order to study further the role of OMT on the autonomic nervous s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(57 citation statements)
references
References 72 publications
(90 reference statements)
3
53
1
Order By: Relevance
“…Interestingly, an increase in measures of vagally mediated HRV obtained via plethysmography was observed during both the 15-min OMT treatment and the following 5 min when no hand contact was provided ( Ruffini et al, 2015 ). These results were recently replicated by the same group ( Cerritelli et al, 2020a ), and appear consistent with HRV responses to other forms of manual therapy, including spinal manipulative therapy and manual cranial therapy, both in asymptomatic adults ( Budgell and Hirano, 2001 ; Budgell and Polus, 2006 ; Welch and Boone, 2008 ) and children ( Bayo-Tallon et al, 2019 ). Together, these studies provide preliminary evidence that manual therapy techniques, and OMT in particular for our purposes, are associated with HRV changes which seem to: (i) be indicative of a larger cardiac vagal modulation under several conditions (i.e., resting and passive standing), (ii) be independent from the part of the body needing treatment, (iii) occur even in the absence of somatic dysfunctions, and (iv) be evident in different age and sex groups.…”
Section: Omt and Hrv In Healthy Subjectssupporting
confidence: 71%
“…Interestingly, an increase in measures of vagally mediated HRV obtained via plethysmography was observed during both the 15-min OMT treatment and the following 5 min when no hand contact was provided ( Ruffini et al, 2015 ). These results were recently replicated by the same group ( Cerritelli et al, 2020a ), and appear consistent with HRV responses to other forms of manual therapy, including spinal manipulative therapy and manual cranial therapy, both in asymptomatic adults ( Budgell and Hirano, 2001 ; Budgell and Polus, 2006 ; Welch and Boone, 2008 ) and children ( Bayo-Tallon et al, 2019 ). Together, these studies provide preliminary evidence that manual therapy techniques, and OMT in particular for our purposes, are associated with HRV changes which seem to: (i) be indicative of a larger cardiac vagal modulation under several conditions (i.e., resting and passive standing), (ii) be independent from the part of the body needing treatment, (iii) occur even in the absence of somatic dysfunctions, and (iv) be evident in different age and sex groups.…”
Section: Omt and Hrv In Healthy Subjectssupporting
confidence: 71%
“…Thinking about these connections and correlating the musculoskeletal system -with all its subdivisions, that include the fascial system-we can suppose that small state growths may be linked to the presence of stress factors. Osteopathic treatment has demonstrated its efficacy in modulating autonomic nervous system function, favoring the enhancement of parasympathetic activity [29,38,39] . In 2019, a study demonstrated a reduction in allostatic biomarkers -evaluation of cortisol, diurnal catecholamines with urine tests, glycated hemoglobin, high-intensity lipoproteins, high reactive protein C sensitivity, blood pressure, BMI and hip-waist index-following osteopathic manipulative treatment [40].…”
Section: Discussionmentioning
confidence: 99%
“…We used direct and indirect techniques that are well-known and described in the literature [6] to make the areas of restriction more compliant and free [28]. The manipulative osteopathic treatment supports the metabolic processes, promotes vascularization and improves ROM [6,13,29] .…”
Section: Therapeutic Interventionmentioning
confidence: 99%
“…Lastly, some evidence shows MTs might help manage essential hypertension as an adjunctive therapy to drugs ( 15 , 16 ), an effect that could be due to the potential ability of MTs to positively affect the autonomic nervous system regulation ( 57 ).…”
Section: The Current State Of the Use Of Mts Vr And Armentioning
confidence: 99%
“…Interestingly, in the last few years, several papers showed that OMT may affect brain activity in both healthy adults ( 57 , 119 ) and patients with chronic LBP ( 110 , 120 ). OMT influenced regional cerebral blood flow, blood oxygen level dependent response and functional connectivity in many cerebrals areas, including the insula, cingulate cortex, amygdala, striatum, caudate, middle frontal and temporal gyri, cerebellum, and prefrontal cortex ( 57 , 110 , 119 , 120 ).…”
Section: The Crossroads Between Mts Vr and Armentioning
confidence: 99%